Efektifitas Poly Aluminium Chloride (PAC) Pada Pengolahan Limbah Lumpur Pemboran Sumur Minyak - Yustinawati Yustinawati; Nirwana Nirwana; Irdoni HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Handling on waste oil drilling mud in research area uses an integrated sludge waste treatment method known as Mud Centralized Treatment Facility (CMTF). One processing stage performed in CMTF is chemical treatment using aluminum sulfate coagulant where the process of coagulation is optimum yet because there were still contain sediment solids. Poly Aluminium Chloride (PAC) thus becomes an alternative coagulant for the treatment because the main properties of colloidal particles in PAC do coagulation in quickly and optimum pace. Research on the “Effectiveness Coagulant Treatment using Poly Aluminium Chloride on Waste Oil Drilling Mud